Various approaches to influence melatonin level in sheep reproduction - Kárpáti, Edina; Fürlinger, Dóra; Móczáné Pleskó, Anikó; Gulyás, László; Gáspárdy, András; BECSKEI, Zsolt (Veterinarski Glasnik, 2023)
A new field of research in reproductive biology was heralded by the discovery of melatonin in 1958. The concentration of melatonin follows light-dark cycles with significantly higher concentrations during darkness. The authors present the importance of the melatonin protein hormone by focusing on the reproductive processes in domestic sheep. In their literature review, they report that sheep melatonin levels show daily and seasonal rhythms. In sheep as a seasonal breeder and short-day animal species, seasonal increases in melatonin production stimulate sexual activity. The authors describe innovative possibilities for regulating melatonin levels in sheep production. The use of exogenous melatonin brings forward the expression of the sexual cycle. It increases the fertility rate, the number of lambs born, and the chances of survival of twin lambs. Melatonin is a neuroprotection compound against cerebral hypoxia and the development of inflammatory processes in the growing foetus and the newborn lamb.